23 A real time data dashboard for smart infusion pump patient data. (15th December 2021) - Batayev, Daulet; Renshaw, Gemma; Ching, Henry; Chen, Tianang; Sridharan, Shankar; Fu, Yun; Mohamedally, Dean; Sebire, Neil J; Visram, Sheena
Abstract : Introduction: Enteral feeding pumps are medical devices used as common practice in hospitals to deliver nutrients and fluids into patients in controlled amounts. This way of feeding is a popular way of supporting children receiving treatment for conditions such as cancer, where side effects of treatment make it difficult to eat and drink well. With the recent developments of smart digital infusion pumps, there is an opportunity to take a data- driven approach when evaluating care plans, particularly for children and young people, who receive this type of treatment at home. Methods: A progressive web application and dashboard was developed using chart.js to visualise data as well as for entering feedback to certain abnormal data points. The backend of the application was developed with Node.js and Express framework and is responsible for authentication, authorisation, fetching data from the infusion pump, treatment plans, and accessing historical data. Security was a priority; therefore, the system uses JWT tokens for authorisation. Results: A proof-of-concept system for clinicians and patients is presented here, which seamlessly generates a real-time dashboard of live data from infusion pumps. This was achieved by developing the frontend in React and used Redux for state management, consisting of five components: authentication system, patient dashboard, clinician dashboard, patient information and treatment history. By co-designing this interface with clinicians to map out an oncology treatment path, new features to annotate and explain interruptions to infusions and analyse long term trends were developed. Conclusion: A dashboard compiled with live data from infusion pumps could speed up the process of decision making and offer actionable insights to clinicians, patients, and their families. This could also encourage the development of a collaborative and personalised treatment plan. Future phases for this project involve integrating FHIR standards into the application, interoperating the system and user experience testing.